PRE-ROTATION OF SUTURE FAILURE DURING SUTURING OF PERFORATED GASTRIC AND DUODENAL ULCERS. (World Bulletin of Public Health, 2025)
Improving the reliability of tightness of sutures when suturing perforated gastric and duodenal ulcers in conditions of widespread peritonitis by improving the method of preventing suture failure.